Mediatization, Politics and the Question of the Publicness - Fernández, Mariano Néstor (2021)
This text reflects on the ‘mediatization of politics’. The following hypothesis is proposed: the problem of ‘mediatization’ in relation to ‘politics’ is not that of the influence of ‘the media’ on political actors and institutions; instead it should be read as a series of successive transformations in the production of the public as a space, as an environment, as a horizon for discourse reception. From this point of view, the widespread association between the ‘media’ and ‘mediatization’ is a historical contingency. Thus, at present, the ‘mediatization of politics’ cannot be considered without incorporating SNS-specific digital platforms as a main determinant. Moreover, platforms also transform the circumstances in which the media themselves (as institutions) are linked to ‘politics’ (other institutions) and to their own audiences. So the advent of the Internet has changed our own understanding of what the ‘media’ is. Ultimately, this paper is an attempt to present a number of reasons why it is necessary to move away from the term ‘mediatization of’ and to argue for the analytical productivity of the concept of ‘public-ness’ in examining the relations between communication technologies, political practices and the media.